Identifying antisense oligonucleotides for targeted inhibition of insulin receptor isoform A - Galifi, Christopher A.; Dikdan, Ryan J.; Kantak, Divyangi; Bulatowicz, Joseph J.; Maingrette, Krystopher; Gunderson, Samuel I.; Wood, Teresa L. (Frontiers in Oncology, 2025)
IntroductionThe insulin receptor (IR) is alternatively spliced into two isoforms, IR-A and IR-B. IR-B is primarily associated with metabolic signaling, whereas IR-A is highly expressed during embryogenesis. IR-A specifically has been associated with several aggressive cancers; however, selective targeting of IR-A has proven difficult due to its homology with IR-B.MethodsWe generated several antisense oligonucleotides (ASOs) that target the exon 10-12 splice junction site present in IR-A, but not IR-B, mRNA. To test the efficacy of the ASOs, we performed lipofectamine transfections of MDA-MB-231 breast cancer, 22Rv1 prostate carcinoma, and Hs822.T Ewing sarcoma cell lines. We also incubated the MDA-MB-231 cell line with the ASOs in the absence of lipofectamine to determine if they are taken into cells unassisted.ResultsOne ASO variant selectively reduced IR-A mRNA levels with minimal impact on IR-B mRNA and significantly reduced total IR protein. The IR-A ASO successfully induced selective IR-A knockdown in MDA-MB-231 breast cancer cells, which was maintained after a one-week incubation with the ASO. The ASO selectively reduced IR-A mRNA when administered to cells in high doses without the use of a vehicle (i.e. gymnotic delivery). The ASO was also effective at reducing IR-A mRNA in Hs822.T Ewing Sarcoma and 22Rv1 prostate carcinoma cells.DiscussionWe have developed an ASO that targets IR-A with minimal off-target knockdown of IR-B. We hypothesize that the IR-A ASO will be a useful research tool and may have therapeutic value by inhibiting the oncogenic functions of IR-A in cancer cells.